KDIGO clinical practice guideline on the evaluation and care of living kidney donors - Lentine, Krista; Zeier, Martin (Transplantation, 2017)
The 2017 Kidney Disease: Improving Global Outcomes (KDIGO) Clinical Practice Guideline on the Evaluation and Care of Living Kidney Donors is intended to assist medical professionals who evaluate living kidney donor candidates and provide care before, during and after donation. The guideline development process followed the Grades of Recommendation Assessment, Development, and Evaluation (GRADE) approach and guideline recommendations are based on systematic reviews of relevant studies that included critical appraisal of the quality of the evidence and the strength of recommendations. However, many recommendations, for which there was no evidence or no systematic search for evidence was undertaken by the Evidence Review Team, were issued as ungraded expert opinion recommendations. The guideline work group concluded that a comprehensive approach to risk assessment should replace decisions based on assessments of single risk factors in isolation. Original data analyses were undertaken to produce a “proof-in-concept” risk-prediction model for kidney failure to support a framework for quantitative risk assessment in the donor candidate evaluation and defensible shared decision making. This framework is grounded in the simultaneous consideration of each candidate's profile of demographic and health characteristics. The processes and framework for the donor candidate evaluation are presented, along with recommendations for optimal care before, during, and after donation. Limitations of the evidence are discussed, especially regarding the lack of definitive prospective studies and clinical outcome trials. Suggestions for future research, including the need for continued refinement of long-term risk prediction and novel approaches to estimating donation-attributable risks, are also provided.